A Study of Women’s Rights and Personal Laws under Different Marriages Laws: Examining the Impact of Marriage Laws on Women's Rights and Equality in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The study of emancipation and increased status enjoyed by women in a society are good indicators of that society's progress. Despite the fact that countries' legal and cultural landscapes have always been impacted by gender, women have always remained a minority group in terms of global power and influence, despite their numerical equality. As long as half of the people is left behind, no country can progress in any way — socially and economically, as well as politically. Any civilization that denies women the fundamental rights of equality and freedom is committing a grave offence against human dignity, human rights, and development. During the Vedic period in India, female brilliance was at its peak however, it has since experienced a steady fall. As soon as we gained our independence, our country's Constitution was amended to include protections for women and children as well as the wonderful concepts of equality, liberty, and social justice. Many laws were created to defend women's rights and promote their dignity in accordance with the Constitution's mandate. The right to equal pay for equal work, maternity benefits, Inheritance ownership or inheritance, and protection against husband cruelty through divorce or judicial separation are a few examples of such legal innovations. As a result of these legislative changes, a false impression has been created about Indian women's place in Indian society. Even while laws have been passed to aid some women, in practise only a small minority have reaped the benefits of those reforms. As a result of the fact that the majority of Indian women are still uneducated and unaware of their legal rights, very few of them own any real estate. As a result, women in India stay at the bottom rungs of society, both economically and socially.